Reproductive behaviour, cutaneous morphology, and skin secretion analysis in the anuran Dermatonotus muelleri - Antoniazzi, Marta Maria; Mailho-Fontana, Pedro Luiz; Nomura, Fausto; Azevedo, Heloisa Bastianon; Pimenta, Daniel Carvalho; Sciani, Juliana Mozer; Carvalho, Fernando Rogério; Rossa-Feres, Denise Cerqueira [UNESP]; Jared, Carlos (Elsevier, 2022)
Despite the common poison and mucous glands, some amphibian groups have differentiated glands associated with reproduction and usually present on the male ventral surface. Known as breeding glands or sexually dimorphic skin glands (SDSGs), they are related to intraspecific chemical communication during mating. Until recently, reproduction associated with skin glands was recognized only in salamanders and caecilians and remained unexplored among anurans. The Brazilian microhylid Dermatonotus muelleri (Muller's termite frog) is known for its very toxic skin secretion. Despite the slippery body, the male adheres to the female back during reproduction, as they have differentiated ventral glands. In this paper, we have gathered data proposing an integrative approach correlated with the species' biology and biochemical properties of their skin secretions. Furthermore, we suggest that the adhesion phenomenon is related to arm shortening and rounded body that make amplexus inefficient, although constituting important adaptive factors to life underground.
Keywords: Biochemistry; Biological sciences; Ecology; Zoology